2005
DOI: 10.1017/s0265021505001171
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ketamine on acute muscular ischaemia reperfusion in rats

Abstract: Ketamine was found to attenuate acute ischaemia-reperfusion injury in muscle tissue in rats (muscular protective). Ketamine may attenuate lipid peroxidation in muscle tissue in tourniquet-requiring manoeuvres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Hct 10 % (CA1: 11,44 ± 2,52; cortex: 13,65 ± 2,31) que dans le groupe Hct 20 % (CA1 : 8,29 ± 1,31 ; cortex : 10,68 ± 1,24 ; P < 0,05) …”
Section: Discussionunclassified
See 1 more Smart Citation
“…Hct 10 % (CA1: 11,44 ± 2,52; cortex: 13,65 ± 2,31) que dans le groupe Hct 20 % (CA1 : 8,29 ± 1,31 ; cortex : 10,68 ± 1,24 ; P < 0,05) …”
Section: Discussionunclassified
“…In the present study, we developed a HCA model using rats, which was designed to mirror clinical circulatory arrest to the greatest extent possible. 11 As with other related rodent models, 23,24 we used chloral hydrate as the primary anesthetic. Our findings provide convincing evidence that low Hct worsens cerebral injury after prolonged HCA.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine has shown protective properties on I/R injury of the brain, 15 kidney, 16 skeletal muscle, 17 and heart, 18 among other tissues. A previous study showed that total ketamine anesthesia reduced intestinal mucosal damage and motility alterations after I/R, in comparison to pentobarbital anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine is a parenteral anesthetic that non-competitively blocks the NMDA receptor [9] . It has been shown that ketamine protects various tissues from I/R injury, such as brain [10] , myocardium [11] and skeletal muscle [12] . To the best of our knowledge, no previous studies have evaluated the effects of ketamine on intestinal motility impairment and tissue damage induced by I/R.…”
Section: Introductionmentioning
confidence: 99%